Learning relay start strategies in swimming: What feedback is best? - Fischer, S.; Braun, C.; Kibele, A. (European Journal of Sport Science, 2017)
In the past, studies and book recommendations on relay starts in swimming have been predominantly focused on the change-over time (COT) as a performance criterion. Aside from the circular backswing start with parallel foot placement, few studies have analysed differences in the take-off movement including step approaches as well. Although trends could be identified, the results remained still somewhat inconclusive. In contrast, no study has examined as has examined whether a reduction of COT in between wall contact of the income swimmer and the take-off of the outgoing swimmer is an optimal relay start strategy, as advocated by various swimming experts. Therefore, the purpose of this study was to compare two different relay start strategies: offensive strategy minimizing COT and conservative strategy to maximize horizontal peak force (HPF). In this regard, a learning intervention with 24 elite-level swimmers (12 females, 12 male) was conducted to compare both strategies regarding relay start time, HPF and COT. Subjects were randomly assigned to two feedback groups: COT versus HPF at take-off. The results of this study showed a clear advantage for HPF feedback for relay start performance measured by wall contact of the incoming swimmer and head passage at 7.5 m of the outgoing swimmer. In addition, similar reductions in COTs were found in both training groups. In conclusion, swimmers should focus on force production rather than minimizing COT. For the latter, deteriorating consequences for force production must be considered.